Beamforming effects on generalized Nakagami imaging. (15th September 2015) - Yu, Xue; Guo, Yuexin; Huang, Sheng-Min; Li, Meng-Lin; Lee, Wei-Ning
Abstract: Ultrasound tissue characterization is crucial for the detection of tissue abnormalities. Since the statistics of the backscattered ultrasound signals strongly depend on density and spatial arrangement of local scatterers, appropriate modeling of the backscattered signals may be capable of providing unique physiological information on local tissue properties. Among various techniques, the Nakagami imaging, realized in a window-based estimation scheme, has a good performance in assessing different scatterer statistics in tissues. However, inconsistent m values have been reported in literature and obtained only from a local tissue region, abating the reliability of Nakagami imaging in tissue characterization. The discrepancies in m values in relevant literature may stem from the nonuniformity of the ultrasound image resolution, which is often neglected. We therefore hypothesized that window-based Nakagami m estimation was highly associated with the regional spatial resolution of ultrasound imaging. To test this hypothesis, our study investigated the effect of beamforming methods, including synthetic aperture (SA), coherent plane wave compounding (CPWC), multi-focusing (MF), and single-focusing (SF), on window-based m parameter estimation from the perspective of the resolution cell. The statistics of m parameter distribution as a function of imaging depth were characterized by their mean, variance, and skewness. The phantom with a low scatterer density (16 scatterers mm −3 ) had significantly lower m values compared to the ones with high scatterer densities (32 and 64 scatterers mm −3 ). Results from the homogeneous phantom with 64 scatterers mm −3 showed that SA, MF, and CPWC had relatively uniform lateral resolutions compared to SF and thus relatively constant m estimates at different imaging depths. Our findings suggest that an ultrasound imaging regime exhibiting invariant spatial resolution throughout the entire imaging field of view would be the most appropriate for Nakagami imaging for tissue characterization.